LOCAL BUSINESS CONCERNS AS ACCOUNTING LABORATORIES. - Blayton, Jesse B. (The Accounting Review, 1935)
Abstract The article discusses the procedure followed by the Atlanta University in providing adequate laboratories to the students. This gave rise to the suggestion that the local business concerns, especially the smaller business units, be turned into a large scale laboratory, in which students under immediate faculty supervision might carry on practical work in the keeping of books. The majority of the students who are enrolled in accounting at Atlanta University seek laboratory assignments. It is increasingly difficult to find sufficient students to keep the books for the concerns which seek their services. In assigning students to business concerns, they are placed so far as possible in the type of concern in which they seem to have the greatest interest. With a list of concerns to select from the student has an opportunity to choose one which is nearest to his liking. One advantage which Atlanta University has over some schools which might undertake a similar project lies in the fact that the professors and instructors in the Department of Business Administration are actually engaged in the operation of successful retail concerns, banks, and accounting firms in the community.